Local Perception and Behavior in Domestic Waste Management and Water Quality of The Brantas River, Dinoyo Ward - Anggayasti, Wresti L.; Al Zamzami, Ilham Misbakudin; Pramudia, Zulkisam; Dwi Susanti, Yogita Ayu; Moehammad, Khibar Syiar; Ulfa, Siti Mariyah; Efani, Anton; Koentjoro, Maharani Pertiwi; Amin, Abd Aziz; Yanuar, Adi Tiya; Salamah, Lutfi Ni’matus; Galisong, Ridwan Danuarta; Aulia, Lisa; Kurniawan, Andi (Postgraduate School of Universitas Brawijaya, 2024)
Waste management by society not only reflects individual responsibility but also plays a crucial role in environmental sustainability and community welfare. This research aimed to understand society’s perception and behavior regarding domestic waste and its surrounding waters. Understanding societal behavior is the key to sustainable environmental management. Direct inquiry was conducted to the sample population of 25 respondents who represented various age, education, and cultural groups in the densely populated residential area surrounding the Brantas River in Dinoyo Ward. Field observations were done to take water quality parameters and monitor the residents’ behavior regarding waste management. The results indicated that 76% of respondents know the impact of river pollution, although most did not contribute actively to reducing their domestic waste volume. About 44% of respondents never saw anyone littering the river, which may be due to the regular waste pick-up system. This was supported by water quality parameters that did not demonstrate any sign of pollution, although high turbidity was indicated. Comprehension of the results of this study is hoped to inspire the ideas of solid intervention plans to increase awareness and decrease the negative impact of domestic waste on the Brantas River in Dinoyo Ward. Keywords: society perception and behavior, domestic waste management, aquatic environment, Brantas River